2017
DOI: 10.1200/jco.2017.35.15_suppl.e18289
|View full text |Cite
|
Sign up to set email alerts
|

Venous thromboembolism incidence in radiation oncology: Retrospective trial.

Abstract: e18289 Background: Venous thromboembolism (VTE) prevention in oncology patients during external beam radiation therapy (RT) in outpatient setting is the challenging question. We performed analysis of our own data. The aim of study is the clear assessment of VTE incidence in these patients Methods: In retrospective analysis 5134 patients' medical records were included (2612 with RT and 2522 with chemotherapy). Inclusion criteria were: RT in outpatient setting and chemotherapy in outpatient setting. Exclusion c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…Actually, when comparing the number of VTE events that were reported, VTE incidences upon RT are quite similar between studies and the present cohort. In the retrospective analysis that assessed VTE incidence in RT‐treated patients versus chemotherapy‐treated patients, four cases were reported in the RT group for body tumors, out of 158 patients, thus suggesting a comparable VTE incidence to our study 26 . By contrast, in the post‐hoc analysis of the COMPASS‐CAT trial, the authors reported a higher VTE incidence of about 9.1%, with 33 events in 336 evaluable patients, considering that all patients were treated by chemotherapy and that 25% of patients were metastatic 27,30 .…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…Actually, when comparing the number of VTE events that were reported, VTE incidences upon RT are quite similar between studies and the present cohort. In the retrospective analysis that assessed VTE incidence in RT‐treated patients versus chemotherapy‐treated patients, four cases were reported in the RT group for body tumors, out of 158 patients, thus suggesting a comparable VTE incidence to our study 26 . By contrast, in the post‐hoc analysis of the COMPASS‐CAT trial, the authors reported a higher VTE incidence of about 9.1%, with 33 events in 336 evaluable patients, considering that all patients were treated by chemotherapy and that 25% of patients were metastatic 27,30 .…”
Section: Discussionsupporting
confidence: 81%
“…18 Moreover, in a retrospective analysis that stratified patients in three groups (i.e., RT for brain tumors, RT for body tumors, chemotherapy-treated brain and body tumors), external beam RT was identified as an independent risk factor for VTE development in outpatient setting, with a risk difference of 5% (p 0.018) in comparison to chemotherapy. 26 Similarly, in a recent sub-analysis of the COMPASS-CAT study, a significant correlation between RT and VTE was described in patients with breast, lung, ovarian or colon cancer (HR 2.47, 95% CI 1.47-4.12, p 0.011). 27 Yet, other studies did not find any specific association between RT and cancer-associated thrombosis.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…A retrospective analysis of outpatient cancer patients, who were treated with RT or chemotherapy, was conducted to assess the impact of RT on the risk of CAT. In this study, patients were divided into three groups including 165 treated with 3-Dimensional conformal RT for brain tumors or brain metastasis (10 patients-around 6% had VTE), 158 treated with RT for body tumors (four patients had VTE), and a third control group including 164 patients treated with chemotherapy (four patients had VTE) [ 15 ]. External beam RT was associated with a significantly increased risk of VTE compared to chemotherapy, with a risk difference of 5% ( p = 0.018).…”
Section: Discussionmentioning
confidence: 99%